Mouse, but Not Human, ApoB-100 Lipoprotein Cholesterol Is a Potent Innate Inhibitor of Streptococcus pneumoniae Pneumolysin - Wade, Kristin R. (Public Library of Science, 2014)
Streptococcus pneumoniae produces the pore-forming toxin pneumolysin (PLY), which is a member of the cholesterol-dependent cytolysin (CDC) family of toxins. The CDCs recognize and bind the 3β-hydroxyl group of cholesterol at the cell surface, which initiates membrane pore formation. The cholesterol transport lipoproteins, which carry cholesterol in their outer monolayer, are potential off-pathway binding targets for the CDCs and are present at significant levels in the serum and the interstitial spaces of cells. Herein we show that cholesterol carried specifically by the ApoB-100-containing lipoprotein particles (CH-ApoB-100) in the mouse, but not that carried by human or guinea pig particles, is a potent inhibitor of the PLY pore-forming mechanism. Cholesterol present in the outer monolayer of mouse ApoB-100 particles is recognized and bound by PLY, which stimulates premature assembly of the PLY oligomeric complex thereby inactivating PLY. These studies further suggest that the vast difference in the inhibitory capacity of mouse CH-ApoB-100 and that of the human and the guinea pig is due to differences in the presentation of cholesterol in the outer monolayer of their ApoB-100 particles. Therefore mouse CH-ApoB-100 represents a significant innate CDC inhibitor that is absent in humans, which may underestimate the contribution of CDCs to human disease when utilizing mouse models of disease.